Physiological implications of NTBI uptake by T lymphocytes - Pinto, Jorge P.; Arezes, João; Dias, Vera; Oliveira, Susana; Vieira, Inês; Costa, Mónica; Vos, Matthijn; Carlsson, Anna; Rikers, Yuri; Rangel, Maria; Porto, Graça (Frontiers in Pharmacology, 2014)
In iron overload disorders a significant fraction of iron circulates in the plasma as low molecular weight complexes not bound to transferrin, known as non-transferrin-bound iron (NTBI). By catalyzing the formation of free radicals, NTBI accumulation results in oxidative stress and cellular damage causing organ toxicity. NTBI is rapidly and preferentially cleared from circulation by the liver and the myocardium, the main disease targets in iron overload conditions. We have recently demonstrated that human peripheral blood T lymphocytes take up NTBI in vitro, with a pattern that resembles that of hepatocytes. Since T lymphocytes constitute a numerically important component of the circulating cell pool, these findings support a putative role for this cell type in the systemic protection against iron toxicity. Here we tested the hypothesis that the circulating peripheral blood T lymphocyte pool constitutes an important storage compartment for NTBI and is thus a modifier of NTBI deposition in target organs. First we show that NTBI uptake by human T lymphocytes increases the expression of the iron-storage protein ferritin and of the iron exporter ferroportin via an IRE-dependent mechanism. NTBI retention by T lymphocytes is shown to be critically controlled by the hepcidin-mediated modulation of ferroportin both in vitro and in vivo. Finally, the protective effect of T lymphocytes was tested by analyzing the patterns of iron accumulation in the T lymphocyte-deficient mouse model Foxn1nu before and after reconstitution with T lymphocytes by adoptive transfer. The results confirmed a significant increase of liver and pancreas iron accumulation in T lymphocyte-deficient mice. NTBI accumulation in the liver and spleen was prevented by reconstitution with syngeneic T lymphocytes. Altogether, our results demonstrate that T lymphocytes are important components of a circulating “NTBI storage compartment” and show its physiological relevance as a modifier of tissue iron overload.